Legal Responsibility of Influencers in Unauthorized Product Endorsements: An Analysis of Toxic Influencer Marketing Practices in Indonesia - Saputra, Vinshen; Putra, Moddy Rizqy Syailendra (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The rise of digital marketing has increased the use of influencers to promote products, including health products, cosmetics, and supplements. The phenomenon of covert endorsement, promoting products without BPOM (Indonesian Food and Drug Authority) approval, poses legal and consumer safety risks. This study analyzes covert endorsement practices within the framework of toxic influencer marketing and examines influencers’ legal accountability under Law No. 17 of 2023 on Health and consumer protection principles. Using normative legal research with statutory, conceptual, and relevant empirical case analysis, the study finds that influencers hold a strategic position in influencing consumer behavior, making a duty of care inherent in their promotional activities. Influencers may be held administratively, civilly, or criminally liable if promoting unregistered products that harm consumers. The study emphasizes the need to strengthen regulations, establish product verification standards, and ensure transparency in promotions to protect the public from toxic influencer marketing risks.